Prevalence of burnout in medical students in Guatemala: Before and during Covid-19 pandemic comparison. (September 2022) - Ruiz, Roxanna; Fernandes, Diego Asturias; Vásquez, Allan; Trigueros, Andrea; Pemberton, Max; Gnanapragasam, Sam N; Torales, Julio; Ventriglio, Antonio; Bhugra, Dinesh
Burnout is a syndrome consisting of physical, emotional, and mental exhaustion along with depersonalization and poor sense of personal accomplishment. Often related to work conditions. Several recent studies from around the world have shown high rates of burnout among medical students in different countries. In Guatemala City, we decided to assess levels of burnout in 2017 and then again in December 2020. In the first wave from one private medical school, we had a total of 159 respondents (response rate of 56.7%) and 132 (48.5%) in the second wave. Not surprisingly rates of burnout were higher during the pandemic even though response rate is lower. Surprisingly we found that rates of depersonalization had not increased, and levels of personal accomplishment had. These findings present a mixed picture of levels of burnout in Guatemala City. Further qualitative research is indicated to explore cultural differences in order to set up appropriate and suitable intervention strategies.